A prospective study on role of dehydroepiandrosterone (DHEA) on improving the ovarian reserve markers in infertile patients with poor ovarian reserve. (November 2013) - Singh, Neeta; Zangmo, Rinchen; Kumar, Sunesh; Roy, K. K.; Sharma, J. B.; Malhotra, Neena; Vanamail, Perumal
Abstract Aim: The aim of this study was to evaluate the role of dehydroepiandrosterone (DHEA) supplementation on the ovarian reserve markers in infertile patients who were poor responders in previous in vitro fertilization (IVF) cycles. Study design: A prospective clinical trial was conducted on 30 patients with history of poor response in previous IVF cycles. These patients were treated with DHEA, (Tab Eema-D, Corona Remedies Pvt Ltd., Ahmedabad, Gujurat, India) 25 mg thrice a day for four months. Ovarian stimulation was done using the previous protocol. Clinical parameters were measured before and treatment with DHEA. Results were analysed using Student's "t" paired test. Results: DHEA resulted in a significant increase (p < 0.05) in the serum Antimullerian hormone in all age groups (35, 36–38 and >38 years). Peak estradiol level on the day of human chorionic gonadotrophin administration also increased significantly (p < 0.05). A significant decrease (p < 0.05) was noted in Day 2 follicle-stimulating hormone (FSH) in all age groups. There was no statistically significant difference in the antral follicle count (AFC). Pregnancy rate was 16.7% after treatment. Thus, DHEA has a significant effect in improving the ovarian reserve in poor responders with previously failed IVF cycles. It can help in enhancing clinical pregnancy rate in these patients.